PENGARUH ONLINECUSTOMERREVIEW, ONLINECUSTOMER RATING DAN LAYANAN CASHONDELIVERY (COD)TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA MARKETPLACE SHOPEE DI KOTA TASIKMALAYA - Eyen Haryanto Yusuf Hanapi; Tin Agustina Karnawati; Mohammad Bukhori (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
The existence of an online review feature (online customer review) is expected to be able to give confidence to potential consumers when looking for and wanting to buy a product. In addition, there are also online reviews (online customer ratings) that can provide benefits as consumer reference material. Not only online customer reviews and online customer ratings are important things when shopping online, but there is a COD (Cash On Delivery) service that makes it easy for buyers to make payments. The existence of online customer reviews, online customer ratings and COD services is expected to influence purchasing decisions. The purpose of this study was to determine and analyze the effect of online customer reviews on purchasing decisions, the effect of online customer ratings on purchasing decisions, and the effect of cash on delivery (COD) services on purchasing decisions for Shopee marketplace users in the city of Tasikmalaya. The method used in this study is a quantitative method with a survey approach, using multiple linear regression analysis and hypothesis testing. The results showed that there was a significant influence of online customer reviews on purchasing decisions, online customer ratings on purchasing decisions and COD